2023
DOI: 10.47134/ijhis.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

File Security Design in Electronic Health Record (EHR) System with Triple DES Algorithm (3DES) at Jember Family Health Home Clinic

Abstract: Electronic Health Record (EHR) is an electronic version of a patient's medical history maintained by a health care service from time to time. The hacking of medical record data by irresponsible parties is a security threat to the EHR system, including the EHR system belonging to the Jember Family Health Home Clinic which is not equipped with a file security system. This research was conducted by designing file security on the EHR system with the Triple DES (3DES) algorithm using UML (Unified Modeling Language)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…AES-128 versus Triple DES evaluates three 64-bit arithmetic ciphers. Yunus et al [12] suggested using the Triple DES (3DES) algorithm to secure medical record data in Jember Family Health Home Clinic's electronic health record system, as shown in Table 1.…”
Section: Related Workmentioning
confidence: 99%
“…AES-128 versus Triple DES evaluates three 64-bit arithmetic ciphers. Yunus et al [12] suggested using the Triple DES (3DES) algorithm to secure medical record data in Jember Family Health Home Clinic's electronic health record system, as shown in Table 1.…”
Section: Related Workmentioning
confidence: 99%